Predictive design of tactile friction for micro/nanostructured haptic surfaces - Yuan Ma; Xinyi Li; Xuezhi Ma; Changhyun Choi; Luke Kruse; Shoufeng Lan; M. Cynthia Hipwell (Communications Materials)
Abstract Design of micro/nanotextured consumer product surfaces presents the opportunity to enrich tactile experiences and enhance the capabilities of haptic devices, enabling rich human-object interactions through the passive or active control of finger friction. The absence of a comprehensive model that can holistically represent the underlying physics at finger-material interface, however, inhibits reliable prediction of finger friction. Here, we develop a model for micro/nanostructured touch interfaces, accounting for contact mechanics, capillaries, electrostatic fields, and their mutual interactions. We experimentally validate this model and apply it to predicting the friction and adhesion of microparticle-coated plastic films for food packaging, and designing surface structures for electroadhesive surfaces to achieve both stronger effects and lower variability — essential features for high-volume consumer electronics. Our model has wide applicability in predictive design of micro/nanostructured surfaces with diverse haptic functionalities.